Comparação entre adultos e idosos internados devido à COVID-19: variáveis da hospitalização e capacidade funcional pós-alta - Lourenço, Andressa Cortez de (Universidade Federal de São Carlos, 2023)
COVID-19 can lead to hospitalization and the use of Invasive Mechanical Ventilation (IMV). However, studies evaluating and comparing the functional capacity of adult and older adults after hospitalization due to COVID-19 are incipient. Objectives: To compare functional capacity through the two-minute Stationary Walking Test (2SWT) and the 30-second Sit and Stand Test (30SST) remotely in adults and older adults after a period of hospitalization due to COVID-19, considering the time of hospitalization and the need for IMV. Methods: This is a retrospective study which used a database of patients assessed remotely after hospital discharge due to COVID-19 was analyzed. 92 patients participated in the study and were divided into two groups, the adult group up to 59 years old (n=62) and the older adults aged 60 years or over (n=30), who underwent 2SWT and 30SST. Results: The mean age of the groups was 54±10.7 years, 57.6% were male, the median hospitalization time was 10 (5–17) days and 45.6% of patients required IMV. It was possible to verify in the teleservice that the adult group presented better performance in the 2SWT in relation to the older adults, with a significant difference in the number of steps (p=0.012), in addition, the elderly desaturated more at the peak of the 2SWT (p=0 .05). No significant differences were observed between groups in 30SST. Conclusion: The adult group showed better performance in 2SWT, with shorter hospitalization time compared to the older adults. Adults and older adults had statistically similar performance on the 2SWT, regardless of the length of hospitalization and use of IMV.
Comparison between adults and older adults hospitalized due to COVID-19: hospitalization variables and post-discharge functional capacity
Keywords: COVID-19; Hospitalização; Teste de Exercício; Telemonitorização; Hospitalization; Exercise testing; Telemonitoring; COVID-19; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL